ANALISIS PENERIMAAN PAJAK DAN REALISASI PAJAK DAERAH TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) DI KOTA BATAM 2011-2015 - Jurnal Akuntansi Barelang (LPPM Universitas Putera Batam, 2017)
The aim of research is to know and analysis the influence of local taxes and local retribution fund to local revenue in batam city. Sample is used are the region’s in come official period 2011-2015.The sampling technique in this study using saturated sampling technique.Methods data analysis in this research is quantitative methods the result of research to shows that local taxes is significant effect to local revenue is caused significant value for 0,000 < 0,05, local retribution is significant effect to local revenue with significant value 0,000 < 0,05, while the local taxes and local retribution fund together are significant effect to local revenue with significant effect 0,000 < 0,05. R square value to shows the variable of local taxes and local retribution fund can to explain variable variance of local revenue for 99,6% while the remaining is 0,4% is effected by the other variable is not researched.